2016
DOI: 10.1093/mnras/stw494
|View full text |Cite
|
Sign up to set email alerts
|

Measuring subhalo mass in redMaPPer clusters with CFHT Stripe 82 Survey

Abstract: We use the shear catalog from the CFHT Stripe-82 Survey to measure the subhalo masses of satellite galaxies in redMaPPer clusters. Assuming a Chabrier Initial Mass Function (IMF) and a truncated NFW model for the subhalo mass distribution, we find that the sub-halo mass to galaxy stellar mass ratio increases as a function of projected halo-centric radius r p , from M sub /M star = 4.43 +6.63 −2.23 at r p ∈ [0.1, 0.3] h −1 Mpc to M sub /M star = 75.40 +19.73 −19.09 at r p ∈ [0.6, 0.9] h −1 Mpc. We also investig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 112 publications
6
66
0
Order By: Relevance
“…After these cuts, the galaxy number density for the source catalog is roughly 4.5 gals/arcmin 2 . Li et al (2016) have compared the lensing signal of CMASS and LOWZ galaxies with source galaxies from different redshift bins and shown that the results agree with each within statistical error bars.…”
Section: Observational Datamentioning
confidence: 83%
“…After these cuts, the galaxy number density for the source catalog is roughly 4.5 gals/arcmin 2 . Li et al (2016) have compared the lensing signal of CMASS and LOWZ galaxies with source galaxies from different redshift bins and shown that the results agree with each within statistical error bars.…”
Section: Observational Datamentioning
confidence: 83%
“…As the CS82 is i-band imaging survey, the photometric redshifts (photo-z) are obtained by using BPZ method (Benítez 2000;Coe et al 2006) and computed by (Bundy et al 2015). Some tests on the systematics induced by photoz error are shown in (Li et al 2016). The total number of source galaxies in this work is 4,381,917.…”
Section: Lensing Shear Catalogmentioning
confidence: 99%
“…Since the lensing and clustering signals of subhaloes are dwarfed by their massive host clusters, it is more difficult to study their detailed mass distributions. Recent progress in determining weak lensing masses of subhaloes has been made by Li et al (2016) using Canada-FranceHawaii Telescope (CFHT) Stripe-82 data (Erben et al 2013) and by Sifón et al (2015) with KiDS data (Kuijken et al 2015). While simulation studies of subhaloes predict that tidal forces from the host cluster will strip mass from the subhalo outskirts (Hayashi et al 2003;Gao et al 2004), the recent lensing studies were not able to identify a tidal radius beyond which mass was stripped.…”
mentioning
confidence: 99%